Can processing of face trustworthiness bypass early visual cortex? A transcranial magnetic stimulation masking study - Janssens, Shanice E.W.; Sack, Alexander T.; Jessen, Sarah; de Graaf, Tom A. (Neuropsychologia, 2020)
As a highly social species, we constantly evaluate human faces to decide whether we can trust someone. Previous studies suggest that face trustworthiness can be processed unconsciously, but the underlying neural pathways remain unclear. Specifically, the question remains whether processing of face trustworthiness relies on early visual cortex (EVC), required for conscious perception. If processing of trustworthiness can bypass EVC, then disrupting EVC should impair subjective (conscious) trustworthiness perception while leaving objective (forced-choice) trustworthiness judgment intact. We applied double-pulse transcranial magnetic stimulation (TMS) to right EVC, at different stimulus onset asynchronies (SOAs) from presentation of a face in either the left or right hemifield. Faces were slightly rotated clockwise or counterclockwise, and were either trustworthy or untrustworthy. On each trial, participants discriminated 1) trustworthiness, 2) stimulus rotation, and 3) reported subjective visibility of trustworthiness. At early SOAs and specifically in the left hemifield, performance on the rotation task was impaired by TMS. Crucially, though TMS also impaired subjective visibility of trustworthiness, no effects on trustworthiness discrimination were obtained. Thus, conscious perception of face trustworthiness (captured by subjective visibility ratings) relies on intact EVC, while objective forced-choice trustworthiness judgments may not. These results are consistent with the hypothesis that objective trustworthiness processing can bypass EVC. For basic visual features, extrastriate pathways are well-established; but face trustworthiness depends on a complex configuration of features. Its potential processing without EVC is therefore of particular interest, further highlighting its ecological relevance. •We investigated the role of EVC in the processing of face trustworthiness using TMS.•TMS to EVC impaired orientation discrimination.•TMS impaired subjective perception of face trustworthiness.•We found no evidence that objective trustworthiness processing was impaired by TMS.•Objective but not subjective trustworthiness processing may proceed without EVC.